PENGARUH FAKTOR INTERNAL DAN EKSTERNAL TERHADAP PROFITABILITAS BANK (Studi Pada Bank Umum Yang Go Public di BEI Periode Tahun 2013-2015) - Rizka Dyah Lukitasari, 14.05.62.0003; Indarti, MG. Kentris (Students' Journal of Accounting and Banking, 2017)
This study examines the factors that affect the profitability of banking companies listed on the IDX period 2013-2015. This research is conducted in Bursa Efek Indonesia by using unit of analysis of banking company. Sampling method using purposive sampling, that is sample determination technique by using certain criteria. The relationship or influence between variables is explained by using multiple linier regression analysis method and hypothesis test (t test). The result of the research shows that variable of Loan to Deposit Ratio (LDR) has positive and insignificant effect to profitability, so hypothesis 1 is unacceptable, Non Performing Loan (NPL) variable has positive and insignificant effect on profitability, so hypothesis 2 Unacceptable, Good Corporate Governance (GCG) variable has a positive and significant influence on profitability, so hypothesis 3 is acceptable, Net Profit Margin (NPM) variable has positive and significant influence to profitability, so hypothesis 4 is acceptable, variable of Capital Adequacy Ratio (CAR) has a negative and significant influence on profitability, so hypothesis 5 is unacceptable, Inflation variables have a negative and significant impact on profitability, so hypothesis 6 is acceptable.Keywords: LDR, NPL, GCG, NPM, CAR, Inflation and Profitability